A PLA durable composition with multi-effect barrier and preparation method thereof
Through the use of composite grafting technology and multi-effect barrier anti-degradation suppressant, the problem of easy decomposition of biodegradable polymer materials has been solved, significantly improving the service life and durability of PLA/PBS materials, realizing its on-market Widely used on.
Patent Information
- Application Number
- CN202210559296.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-05-20
AI Technical Summary
Existing biodegradable polymer materials are easily decomposed under external environmental factors, resulting in a short service life of the product and cannot effectively replace traditional petroleum-based plastics, limiting their wide application in the market.
Using multi-effect barrier PLA durable composition, PLA and PBS resins are modified through composite grafting technology, and a variety of barrier anti-degradation relieving agents and dynamic crosslinking agents are added to form good compatibility and ladders. The composition of the form of release protection enhances its tensile strength, barrier effect and heat resistance.
It significantly improves the service life of the composition, enhances resistance to water, gas, oxygen, microorganisms and light, extends the durability of the product, and realizes the durable application of PLA/PBS materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of biodegradable polymer materials, and in particular to a PLA durable composition with multiple barrier effects and a preparation method thereof. Background Art
[0002] With the rapid development of the national economy, the use of polymer materials has penetrated into all areas of people's lives. For example, plastic products have brought great convenience to our lives. Today, there are many types of plastics, including polyolefins, polyesters, nylons, polystyrene, etc., which have strong mechanical properties, wide applications, and low prices. Therefore, petroleum-based plastics have been widely used in all walks of life and have even become rampant. In particular, the rise of online shopping and takeout has caused these non-degradable traditional petroleum-based plastics to form "white pollution" that damages the ecological environment, and further threatens and harms various organisms and even humans through the food chain.
[0003] Therefore, promoting "green biodegradable polymers" has become the best solution to "plastic waste". In addition, since the carbon footprint of bio-based biodegradable plastics is much lower than that of petroleum-based plastics, it is conducive to the national carbon compliance and carbon neutrality policies. Therefore, using biodegradable plastics to replace traditional plastics that rely on petroleum resources is an important task that cannot be delayed.
[0004] Among various commercialized biodegradable plastics (such as PLA, PBAT, PBS, PCL, PHB, etc.), PLA has the greatest potential and prospects because it has the best average physical properties, relatively low cost, mature mass production technology, and is a plant-based circular economy material that can be planted and regrown.
[0005] However, due to the disadvantages of insufficient physical properties and high cost of current biodegradable plastics, they can only be promoted on disposable products for the time being, which makes the important task of replacing traditional petroleum-based plastics and reducing carbon emissions slow. At the same time, because biodegradable plastics are easily induced by external environmental factors to break and decompose molecular chains, the service life of the product is relatively short, which is another disadvantage that biodegradable plastics cannot quickly open up more uses in the current market. Therefore, it is urgent to develop a durable polymer composition that is both biodegradable and has high physical strength to promote the development and application of biodegradable polymers. Summary of the invention
[0006] In order to solve the technical problem that existing biodegradable polymers cannot maintain stable physical properties for a long time, the present application provides a multi-effect barrier PLA durable composition, comprising the following components in parts by weight: 6 to 55 parts of modified PLA resin, 6 to 25 parts of modified PBS resin, 5 to 20 parts of EVOH-TPU elastomer, 2 to 8 parts of a first barrier anti-degradation sustained-release agent, 2 to 10 parts of a second barrier anti-degradation sustained-release agent, 2 to 8 parts of a comprehensive additive, and 0.5 to 2 parts of a dynamic cross-linking agent.
[0007] Preferably, the modified PLA resin comprises the following components in parts by weight: 80-100 parts of PLA resin, 4-9 parts of maleic anhydride, 0.5-2 parts of ultrafine tourmaline powder with vacuum sputtering deposited nanoparticles on the surface, 0.5-2 parts of ATBC, 0.5-2 parts of KH550 silane coupling agent, 0.02-0.05 parts of DCP diisopropylbenzene peroxide, 0.5-1 parts of 1010 antioxidant, and 0.5-1 parts of 168 antioxidant.
[0008] Preferably, the modified PBS resin comprises the following components in parts by weight: 80-100 parts of PBS resin, 4-9 parts of maleic anhydride, 0.5-2 parts of ultrafine tourmaline powder with vacuum sputtering deposited nanoparticles on the surface, 0.5-2 parts of plasticizer, 0.5-2 parts of coupling agent, 0.02-0.05 parts of DCP diisopropylbenzene peroxide, and 1-2 parts of antioxidant.
[0009] Preferably, the vacuum sputtering deposited nanomaterial on the surface of the ultrafine tourmaline powder is TiOx and / or SiOx, wherein x=0.5, or x=1, or x=1.5, or x=2.
[0010] Preferably, the first barrier anti-degradation sustained-release agent comprises the following components in parts by weight: 80-100 parts of organic montmorillonite, 8-10 parts of nano zinc oxide, 15-20 parts of chitosan, 2-5 parts of PE wax, 5-10 parts of silane coupling agent, 5-10 parts of modified PLA resin, 5-10 parts of modified PBS resin, 5-10 parts of water repellent, 2-5 parts of carbodiimide, 2-6 parts of antioxidant, and 1-2 parts of MDI diphenylmethane diisocyanate.
[0011] Preferably, the second barrier anti-degradation sustained-release agent comprises the following components in parts by weight: 20-70 parts of PVA polyvinyl alcohol, 20-70 parts of corn starch, 10-20 parts of polysaccharide, 0.5-2 parts of cross-linking agent, 2-30 parts of plasticizer, 0.5-2 parts of film-forming agent, 400-800 parts of deionized water, 0.5-2 parts of anti-aging agent, 0.5-2 parts of antioxidant, 0.5-2 parts of heat stabilizer, and 0.5-2 parts of antibacterial agent.
[0012] Preferably, the present application provides a method for preparing a PLA durable composition with multiple-effect barriers, which is used to prepare the above-mentioned PLA durable composition with multiple-effect barriers, comprising the following steps:
[0013] Activation and composite modification steps are used to perform new activation and composite grafting modification treatments on PLA and PBS resins;
[0014] The first barrier and anti-degradation sustained-release agent preparation step is used to prepare a sustained-release agent with barrier and anti-degradation properties;
[0015] The second barrier and anti-degradation sustained-release agent preparation step is used to prepare another barrier and anti-degradation sustained-release agent;
[0016] An elastomer preparation step for preparing a crack-resistant EVOH-TPU elastomer;
[0017] The composition preparation step is used to extrude and granulate the above ingredients to obtain a PLA durable composition with multiple barrier effects.
[0018] Preferably, the activation and composite modification step comprises the following steps:
[0019] The first solid phase grafting of A1, PLA or PBS:
[0020] a1. Add 80-100 parts of PLA or PBS resin into a vacuum dryer, set the drying temperature to 60-80°C, stir at a speed of 400-800 r / min, and start the UV light irradiation in the dryer. While vacuum drying, perform light activation on the surface of the PLA or PBS resin for 1-1.5 hours.
[0021] a2. Stop drying and irradiation and open the cover, add 2-5 parts of maleic anhydride and 0.5-2 parts of ultrafine tourmaline powder with vacuum sputtering deposition nanometers on the surface, mix the above materials, add 0.5-2 parts of ATBC and 0.5-2 parts of silane coupling agent, continue heating and drying and UV light irradiation for 20-60 minutes to connect maleic anhydride to the surface of PLA, and the first stage of solid phase grafting of PLA or PBS is completed:
[0022] A2, the first solid phase grafting of PLA or PBS:
[0023] The first solid-phase grafted PLA or PBS resin prepared in step a2 is transferred into a high-speed mixer, and then 2 to 4 parts of maleic anhydride, 0.02 to 0.05 parts of DCP, 0.5 to 1 parts of antioxidant 1010, and 0.5 to 1 parts of antioxidant are added; the mixture is mixed for 10 minutes, and finally the mixture is put into a twin-screw extruder and granulated at a temperature of 160 to 185° C. to obtain a low-initiator high-activity composite grafted modified PLA or PBS resin.
[0024] Preferably, the first step of preparing the barrier anti-degradation sustained-release agent comprises the following steps:
[0025] B1. Add 80-100 parts of organic montmorillonite, 8-10 parts of nano zinc oxide, 15-20 parts of chitosan, and 2-5 parts of PE wax into a high-speed mixer and mix them at a speed of 800-1000 r / min for 20-30 minutes;
[0026] B2. Pour 5-10 parts of silane coupling agent, 5-10 parts of modified PLA, 5-10 parts of modified PBS, 5-10 parts of water repellent, 2-5 parts of carbodiimide, 2-6 parts of antioxidant 1010, 2-6 parts of antioxidant B225, and 1-2 parts of MDI diphenylmethane diisocyanate, continue to mix at high speed for 10-20 minutes, and then feed the material into a twin-screw granulator to make particles, thus obtaining the first barrier anti-degradation sustained-release agent.
[0027] Preferably, the second step of preparing the barrier anti-degradation sustained-release agent comprises the following steps:
[0028] C1. Take 20-70 parts of PVA polyvinyl alcohol, 20-70 parts of corn starch, 10-20 parts of polysaccharide, 0.5-2 parts of cross-linking agent, 2-30 parts of plasticizer, 0.5-2 parts of film-forming agent, 400-800 parts of deionized water, 0.5-2 parts of anti-aging agent, 0.5-2 parts of antioxidant, 0.5-2 parts of thermal stabilizer, and 0.5-2 parts of antibacterial agent, and mix the above components to obtain a mixed solution.
[0029] C2. Heat the mixed solution to 70-90°C, and stir at a speed of 50-150 r / min for 50-60 minutes, then pour it onto a glass plate, cast it into a film, let it cool for 2-3 days, and then crush the film and sieve it into 200-500 mesh particles to obtain the second barrier anti-degradation sustained-release agent.
[0030] Preferably, the elastomer preparation step comprises the following steps:
[0031] D1. Add 80-100 parts of EVOH resin into the vacuum dryer, set the drying temperature to 70-80℃, turn on the stirring blade (400-600rpm), and start the UV light irradiation in the dryer. While vacuum drying, the surface of the EVOH resin is activated by light for 1-2 hours.
[0032] D2. Stop drying and irradiation, open the cover, add 2-5 parts of maleic anhydride MAH, 0.5-2 parts of ultrafine tourmaline powder with vacuum sputtering deposition nanometers on the surface, add 0.5-2 parts of PVA aqueous solution and 0.5-2 parts of silane coupling agent KH550 after mixing, continue heating and drying and UV light irradiation for 1-2 hours, so that the surface of EVOH resin is connected with MAH, that is, the solid phase grafting of EVOH resin is completed;
[0033] D3. Take 30 parts of the solid-phase grafted EVOH resin obtained in step D2 and 70 parts of TPU resin, blend them for 10 minutes, and put them into twin-screw extrusion granulation (170-185°C) to obtain a crack-resistant EVOH-TPU elastomer.
[0034] Preferably, the composition preparation step comprises the following steps:
[0035] Take 6-55 parts of modified PLA, 10-20 parts of modified PBS, 5-20 parts of EVOH-TPU elastomer, 2-8 parts of the first barrier anti-degradation sustained-release agent, 2-10 parts of the second barrier anti-degradation sustained-release agent, 2-8 parts of comprehensive additives, and 0.5-2 parts of dynamic cross-linking agent;
[0036] The above ingredients are put into a high-speed mixer for compounding and mixing for 10 to 20 minutes, and then fed to a twin-screw melt dynamic cross-linking extrusion granulation, wherein the melt temperature is set at 180-188°C and the melt pressure is set at 2.5-3.5MPa, to obtain a PLA durable composition with multi-effect barrier.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) In order to form a good binding force between the polymers, composite activation grafting is performed on each polymer. At the same time, tourmaline powder with nano-deposited on the surface is mixed before the resin is grafted. PLA resin and PBS resin are composite grafted with grafting materials (MAH and GMA) and subjected to twin-screw reaction extrusion. This unique composite grafting greatly improves the compatibility between different polymers.
[0039] (2) Multi-effect step-by-step release barrier and anti-cracking protective agent: The first barrier anti-degradation slow-release agent is inserted into the montmorillonite by intercalation and then wrapped by PLA / PBS resin. The second barrier anti-degradation slow-release agent is first melted in the cast film, then the film is crushed and ground, and finally melted in the composition. The above comprehensive barrier anti-degradation slow-release agent will be slowly released at different times after the composition is melt-granulated and processed for the second time, forming a gradient long-term effective protection for the final product, achieving the purpose of durable use.
[0040] (3) The polymers of each component are first innovatively grafted and modified, and after mixed melting, excellent bonding forces are generated between the different polymers inside. Finally, the network crosslinking of the entire mixture is strengthened by dynamic crosslinking. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0042] In order to solve the above technical problems, the present application provides a PLA durable composition with multi-effect barrier.
[0043] The invention comprises the following components in parts by weight: 6-55 parts of modified PLA resin, 6-25 parts of modified PBS resin, 5-20 parts of EVOH-TPU elastomer, 2-8 parts of the first barrier anti-degradation sustained-release agent, 2-10 parts of the second barrier anti-degradation sustained-release agent, 2-8 parts of comprehensive auxiliary agent and 0.5-2 parts of dynamic cross-linking agent.
[0044] The modified PLA resin includes the following components in parts by weight: 80-100 parts of PLA resin, 4-9 parts of MAH maleic anhydride, 0.5-2 parts of ultrafine tourmaline powder with vacuum sputtering deposited nano-powder on the surface, 0.5-2 parts of ATBC, 0.5-2 parts of KH550 silane coupling agent, 0.02-0.05 parts of DCP diisopropylbenzene peroxide, 0.5-1 parts of 1010 antioxidant, and 0.5-1 parts of 168 antioxidant.
[0045] The modified PBS resin comprises the following components in parts by weight: 80-100 parts of PBS resin, 4-9 parts of GMA (glycidyl methacrylate), 0.5-2 parts of ultrafine tourmaline powder with vacuum sputtering deposited nanometers on the surface, 0.5-2 parts of ATBC, 0.5-2 parts of KH550 silane coupling agent, 0.02-0.05 parts of DCP diisopropylbenzene peroxide, 0.5-1 parts of 1010 antioxidant, and 0.5-1 parts of 168 antioxidant.
[0046] The present application modifies PBS resin and PLA resin by composite grafting technology, which adopts solid grafting combined with melt grafting. The solid grafting method has the advantages of low temperature and extremely low initiator, but its disadvantage is long reaction time; while the melt grafting method has the advantage of short reaction time, but the residual initiator continuously decomposes the resin matrix, and the grafting temperature is high, and the product produces a strong irritating taste, etc. For this reason, the present application scheme uses modified tourmaline powder to replace the initiator in the front-stage solid-phase grafting process, and the vacuum sputtering deposition nanometer is formed on the surface of the ultrafine tourmaline powder, wherein the vacuum sputtering deposition nanometer material is TiOx and / or SiOx, wherein x=0.5, or x=1, or x=1.5, or x=2. By using modified tourmaline powder to replace the initiator in the front-stage solid phase grafting process, and also using modified tourmaline powder in the back-stage traditional grafting melt grafting method, the amount of initiator is reduced to less than 5% of the traditional method. As a result, the grafting effect is much higher than that of the single grafting method, and the process is very environmentally friendly. A special multi-stage composite grafting process is used to activate or increase the volume of the component polymers in the composition, so that the bonding between the polymers or between the polymers and the fillers can be improved, thereby improving the performance of the composition.
[0047] The first barrier anti-degradation sustained-release agent includes the following components in parts by weight: 80-100 parts of organic montmorillonite, 8-10 parts of nano zinc oxide, 15-20 parts of chitosan, 2-5 parts of PE wax, 5-10 parts of silane coupling agent, 5-10 parts of modified PLA resin, 5-10 parts of modified PBS resin, 5-10 parts of water repellent, 2-6 parts of 1010 antioxidant, 2-6 parts of B225 (BASF) antioxidant, and 1-2 parts of MDI diphenylmethane diisocyanate. Among them, montmorillonite (MMT) is a low-cost and widely available layered clay. By using intercalation technology, water-resistant, antibacterial, anti-aging and other additives can be pre-inserted into the modified montmorillonite to form various slow-release barrier protective substances, forming an organic montmorillonite with slow-release barrier function. The above components are used to prepare a functional organic montmorillonite, which is added to the subsequently modified PLA and PBS resin base materials to form a PLA durable composite with multi-effect barriers, which can effectively enhance the tensile strength and rigidity, improve the barrier effect against water and gas, improve the heat resistance and stability of the base resin, and give the base resin antibacterial properties.
[0048] The second barrier anti-degradation sustained-release agent includes the following components in parts by weight: 20-70 parts of PVA polyvinyl alcohol, 20-70 parts of corn starch, 10-20 parts of polysaccharide, 0.5-2 parts of cross-linking agent, 2-30 parts of plasticizer, 0.5-2 parts of film-forming agent, 400-800 parts of deionized water, 0.5-2 parts of anti-aging agent (UV531), 0.5-2 parts of antioxidant (Ciba1010), 0.5-2 parts of thermal stabilizer (Irganox B215), and 0.5-2 parts of antibacterial agent (nano silver ion).
[0049] Adding the above two barrier anti-degradation slow-release agents can improve the resistance of the prepared composition to moisture, oxygen, microorganisms, light and heat, thereby reducing the degradative effect and extending the ultimate service life of the composition.
[0050] On the other hand, the present application provides a method for preparing a PLA durable composition with multiple-effect barriers, which is used to prepare the above-mentioned PLA durable composition with multiple-effect barriers, comprising the following steps:
[0051] Step 1: Activation and composite modification step, used to perform new activation and composite grafting modification treatment on PLA and PBS resins;
[0052] Step 2: the first barrier and anti-degradation sustained-release agent preparation step, which is used to prepare a sustained-release agent with barrier and anti-degradation properties;
[0053] Step 3: a second barrier and anti-degradation sustained-release agent preparation step, which is used to prepare another barrier and anti-degradation sustained-release agent;
[0054] Step 4: Elastomer preparation step, used to prepare crack-resistant EVOH-TPU elastomer;
[0055] Step 5: a composition preparation step, which is used to extrude and granulate the above ingredients to obtain a PLA durable composition with multiple barrier effects.
[0056] Specifically, the present application modifies PBS resin and PLA resin by composite grafting technology, and the first step of activation and composite modification includes the following steps:
[0057] The first solid phase grafting of A1, PLA or PBS:
[0058] a1. Add 80-100 parts of PLA or PBS resin into a vacuum dryer, set the drying temperature to 60-80°C, stir at a speed of 400-800 r / min, and start the UV light irradiation in the dryer. While vacuum drying, perform light activation on the surface of the PLA or PBS resin for 1-1.5 hours.
[0059] a2. Stop drying and irradiation and open the cover, add 2-5 parts of maleic anhydride or 2-5 parts of GMA, 0.5-2 parts of ultrafine tourmaline powder with vacuum sputtering deposition nanometers on the surface, mix the above materials, add 0.5-2 parts of ATBC plasticizer, 0.5-2 parts of silane coupling agent KH550, continue heating and drying and UV light irradiation for 20-60 minutes, so that the PLA surface is connected with maleic anhydride, and the first stage of solid phase grafting of PLA or PBS is completed:
[0060] Wherein, the vacuum sputtering deposited nanomaterial is TiOx and / or SiOx, wherein x=0.5, or x=1, or x=1.5, or x=2. By using modified tourmaline powder to replace the initiator in the first stage of solid phase grafting process, and also using modified tourmaline powder in the traditional grafting melt grafting method in the latter stage, the amount of initiator is reduced to less than 5% of the traditional method, and the grafting effect is much higher than that of the single grafting method, and the process is very environmentally friendly. In addition, the tourmaline powder is preliminarily in a vacuum furnace, combined with oxygen as the working fluid, and the surface is sputtered and coated with a titanium silicon alloy target, wherein the vacuum sputtering deposited nanomaterials of the present application are TiO2 and SiO2, and the ratio is 1:1.
[0061] A2, the second solid phase grafting of PLA or PBS:
[0062] The first stage of solid phase grafted PLA or PBS resin prepared in step a2 is transferred into a high-speed mixer, and then 2-4 parts of maleic anhydride or 2-4 parts of GMA, 0.02-0.05 parts of DCP diisopropylbenzene peroxide, 0.5-1 parts of antioxidant 1010, and 0.5-1 parts of antioxidant 168 are added, and mixed for 10 minutes. Finally, the mixture is put into a twin-screw extruder, and granulated at a temperature of 160-185°C to obtain a low-initiator high-activity composite grafted modified PLA or PBS resin. The PLA or PBS resin modified by the above steps is a solid phase-melt phase composite two-stage efficient grafting product, which achieves the purpose of improving the bonding force between polymers or between polymers and fillers, thereby improving the performance of the composition. It should be noted that the modification process of PLA resin is mostly the same as that of PBS resin, except that maleic anhydride is used in the modification process of PLA resin, and GMA is used in the modification of PBS resin.
[0063] Furthermore, the first barrier anti-degradation sustained-release agent preparation step comprises the following steps:
[0064] B1. Add 80-100 parts of organic montmorillonite, 8-10 parts of nano zinc oxide, 15-20 parts of chitosan, and 2-5 parts of PE wax into a high-speed mixer and mix them at a speed of 800-1000 r / min for 20-30 minutes;
[0065] B2, pour in 5-10 parts of silane coupling agent, 5-20 parts of modified PLA, 5-20 parts of modified PBS, 5-10 parts of water repellent, 2-6 parts of antioxidant 1010, 2-6 parts of antioxidant B225 (BASF), and 1-2 parts of MDI diphenylmethane diisocyanate, continue to mix at high speed for 10-20 minutes, and then feed the material into a twin-screw granulator to make particles (extrusion temperature 160-190°C), that is, the first barrier anti-degradation sustained-release agent is obtained, hereinafter represented by C1.
[0066] In this step, the organic montmorillonite is modified by the melt intercalation method for the first intercalation of nano zinc oxide and chitosan; then the silane coupling agent, modified PLA and modified PBS are added for the second intercalation modification. The first intercalation is completed in a high-speed mixer, and the second intercalation is completed in a twin-screw extruder granulator to obtain a nano clay intercalation type anti-degradation agent, which is the first barrier anti-degradation sustained-release agent. It can effectively enhance the tensile strength and rigidity of the composition, improve the barrier effect against water and gas, improve the heat resistance stability of the matrix resin, and give the matrix resin antibacterial properties.
[0067] Step 3, the second barrier anti-degradation sustained-release agent preparation step comprises the following steps:
[0068] C1. Take 20-70 parts of PVA polyvinyl alcohol, 20-70 parts of corn starch, 10-20 parts of polysaccharide, 0.5-2 parts of crosslinking agent, 2-30 parts of plasticizer, 0.5-2 parts of film former, 400-800 parts of deionized water, 0.5-2 parts of anti-aging agent (UV531), 0.5-2 parts of antioxidant (Ciba1010), 0.5-2 parts of thermal stabilizer (Irganox B215), 0.5-2 parts of antibacterial agent (nano silver ion), put the above components into a high-speed mixer and mix them, then dilute with deionized water to a mixed solution with a concentration of 30-40%. The PVA brand is polyvinyl alcohol 0580, and the starch is the original starch of corn, cassava, and potato.
[0069] C2. Heat the above mixed solution to 70-90°C, and stir at a speed of 50-150 r / min for 50-60 minutes, then pour it onto a glass plate, cast it into a film, let it cool for 2-3 hours, then crush the film and sieve it into 200-500 mesh particles to obtain a second barrier anti-degradation sustained-release agent, hereinafter referred to as C2.
[0070] Among them, polyvinyl alcohol (PVA) is a biodegradable polymer material with good water solubility and film-forming properties. On the one hand, it has excellent barrier properties to oxygen, carbon dioxide, etc., but on the other hand, it has very good water vapor permeability. Starch is also a biodegradable material, which is extremely convenient to source and is a natural renewable resource. We can use polyvinyl alcohol, starch and chitosan, three materials that are easy to form a film, to blend, and add plasticizers, crosslinking agents, film-forming agents, and slow-release comprehensive anti-degradation agents (including antioxidants, anti-aging agents, thermal stabilizers, etc.). After the raw materials are mixed in a high-speed mixer, they are diluted with deionized water to a concentration of 30-40%, heated to 70-90°C and stirred, and can be poured on a glass sheet and cast into a film. This PVA, starch, and chitosan are low in cost, simple to operate, and easy to deliquescence. After the membrane is crushed and ground, powder particles of about 200 mesh size can be obtained. When the powder particles are penetrated by external water vapor and gradually dissolved, the internal anti-decomposition protective agent can be gradually released into the PLA and PBS matrix resins, enhancing the multiple protections against aging, water vapor and bacteria, thereby delaying the degradation time of the PLA / PBS matrix.
[0071] Step 4, the step of preparing the anti-cracking elastomer comprises the following steps:
[0072] D1. Add 80-100 parts of EVOH resin into the vacuum dryer, set the drying temperature to 70-80°C, stir at a speed of 400-600rpm / min, and start the UV light irradiation in the dryer. While vacuum drying, the surface of the EVOH resin is activated by light for 1-2 hours.
[0073] D2. Stop drying and irradiation, open the cover, add 2-5 parts of maleic anhydride MAH, 0.5-2 parts of ultrafine tourmaline powder with vacuum sputtering deposition nanometers on the surface, add 0.5-2 parts of PVA aqueous solution and 0.5-2 parts of silane coupling agent KH550 after mixing, continue heating and drying and UV light irradiation for 1-2 hours, so that the surface of EVOH resin is connected with MAH, that is, the solid phase grafting of EVOH resin is completed;
[0074] D3. Take 30 parts of the solid-phase grafted EVOH resin obtained in step D2 and 70 parts of TPU resin, blend them for 10 minutes, put them into twin-screw extrusion granulation, set the melt temperature to 170-185°C, and obtain a crack-resistant EVOH-TPU elastomer.
[0075] Step 5, the composition preparation step comprises the following steps:
[0076] Take 6-55 parts of modified PLA, 10-20 parts of modified PBS, 5-20 parts of EVOH-TPU elastomer, 2-8 parts of the first barrier anti-degradation slow-release agent, 2-10 parts of the second barrier anti-degradation slow-release agent, 2-8 parts of comprehensive additives, 0.5-2 parts of dynamic crosslinking agent; 5 parts of talcum powder, 15 parts of calcium carbonate, wherein the components of the comprehensive additives include: 0.5% aluminate coupling agent, 0.5% stearic acid, 0.5% antioxidant 1010, 0.5% anti-aging agent UV531, 1% water repellent. The dynamic crosslinking agent is crosslinking agent MDI (diphenylmethylmethane diisocyanate).
[0077] The above ingredients are put into a high-speed mixer for compounding and mixing for 10 to 20 minutes, and then fed to a twin-screw melt dynamic cross-linking extrusion granulation, wherein the melt temperature is set at 180-188°C and the melt pressure is set at 2.5-3.5MPa, to obtain a PLA durable composition with multi-effect barrier.
[0078] The following comparison between Example 1 and Comparative Example 1 highlights the advantages of the two-stage grafting method (solid-phase grafting combined with melt grafting) of the present invention.
[0079] Embodiment 1
[0080] The steps of activation and composite modification of PLA resin and PBS resin in step 1 of this embodiment are as follows:
[0081] The first stage of solid phase grafting: a1, put 100 parts of PLA resin into a vacuum dryer, set the drying temperature to 60°C, and stir at a speed of 600r / min. At the same time, start the UV light irradiation in the dryer with an intensity of 100W, and perform vacuum drying while performing light activation on the surface of the PLA resin for 1 hour;
[0082] a2. Stop drying and irradiation and open the cover, add 3 parts of maleic anhydride and 0.8 parts of ultrafine tourmaline powder with vacuum sputtering deposition nanometers on the surface, mix the above materials, add 0.5 parts of ATBC plasticizer and 0.5 parts of silane coupling agent KH550, continue heating and drying and UV light irradiation for 60 minutes, so that the maleic anhydride is connected to the surface of PLA, and the first stage of solid phase grafting of PLA is completed:
[0083] The second stage solid phase grafting: the first stage solid phase grafted PLA resin prepared in step a2 is transferred into a high-speed mixer, and then 2 parts of maleic anhydride, 0.02 parts of DCP diisopropylbenzene peroxide, 0.5 parts of antioxidant 1010, and 0.5 parts of antioxidant 168 are added, and mixed for 10 minutes. Finally, the mixture is put into a twin-screw extruder and granulated at a temperature of 160-185° C. to obtain a low-initiator high-activity composite grafted modified PLA resin.
[0084] In the modification step of PBS resin, maleic anhydride was replaced with GMA, and other raw materials and parameters were the same, and finally modified PLA resin and modified PBS resin were obtained.
[0085] Step 2, the preparation step of the first barrier anti-degradation sustained-release agent (C1) comprises the following steps:
[0086] B1. Add 100 parts of organic montmorillonite, 10 parts of nano zinc oxide, 20 parts of chitosan, and 5 parts of PE wax into a high-speed mixer and mix at a speed of 1000r / min for 20 minutes to complete the first intercalation modification.
[0087] B2. Pour in 10 parts of silane coupling agent, 20 parts of modified PLA, 20 parts of modified PBS, 5 parts of water repellent, 2 parts of antioxidant 1010, 2 parts of antioxidant B225 (BASF), and 1 part of MDI diphenylmethane diisocyanate, continue mixing at high speed for 10 to 20 minutes, and then feed the material into a twin-screw granulator to make particles (extrusion temperature 160-190°C), thus obtaining the first barrier anti-degradation sustained-release agent (C1).
[0088] Step 3, the preparation step of the second barrier anti-degradation sustained-release agent (C2) comprises the following steps:
[0089] C1. Take 30 parts of PVA polyvinyl alcohol, 70 parts of corn starch, 12 parts of silan, 0.5 parts of cross-linking agent, 5 parts of plasticizer (sorbitol), 1.5 parts of film-forming agent (silica sol), 700 parts of deionized water, 1.2 parts of anti-aging agent (UV531), 1.2 parts of antioxidant, 1.2 parts of thermal stabilizer, 1.2 parts of antibacterial agent (nano silver ion), PVA brand is polyvinyl alcohol 0580, starch is corn, cassava, potato starch, put the above components into a high-speed mixer and mix them, then add deionized water to dilute it into a mixed solution with a mass concentration of 30-40%.
[0090] C2. Heat the above mixed solution to 80°C, stir at a speed of 120r / min for 60 minutes, then pour it onto a glass plate to form a film, and place it to cool for 2 hours. Then crush the film and sieve it into 400-500 mesh particles to obtain the second barrier anti-degradation sustained-release agent (C2).
[0091] It should be noted that this embodiment 1 does not include the preparation of the anti-cracking elastomer in step 4.
[0092] Step 5, the composition preparation step comprises the following steps:
[0093] Take 51 parts of modified PLA, 20 parts of modified PBS, 3 parts of the first barrier anti-degradation sustained-release agent, 3 parts of the second barrier anti-degradation sustained-release agent, 3 parts of ADX1 comprehensive additive, 5 parts of talc, and 15 parts of calcium carbonate. In this embodiment 1, no dynamic crosslinking agent is added.
[0094] The above ingredients were put into a high-speed mixer for compounding and mixing for 15 minutes, and then fed to a twin-screw extruder for granulation to obtain a PLA durable composite product with multiple-effect barrier properties, with the product code being P1.
[0095] Comparative Example 1
[0096] The steps in Control Example 1 are mostly the same as those in Example 1, but the PLA and PBS resin in Control Example 1 are grafted using the traditional one-step method.
[0097] Step 1: Modify PLA resin and PBS resin by traditional one-step grafting, the steps are:
[0098] (1) First, put 100 parts of PLA resin into the vacuum dryer, set the drying temperature to 60 degrees C, stir at a speed of 600 r / min, and perform vacuum drying for 1 hour;
[0099] The dried mixture was put into a high-speed mixer, and then 3 parts of maleic anhydride (MAH), 0.8 parts of DCP, 0.5 parts of antioxidant 1010, and 0.5 parts of antioxidant 168 were added; mixed for another 10 minutes, and finally the mixture was fed into a twin-screw extruder and granulated at 160-185°C to obtain high-activity M-PLA.
[0100] (2) First, put 100 parts of PBS resin into the vacuum dryer and set the drying temperature to 70 degrees C. Stir at a speed of 600 r / min and perform vacuum drying for 1 hour;
[0101] The dried mixture was put into a high-speed mixer for mixing, and then 3 parts of GMA, 0.8 parts of DCP, 0.5 parts of antioxidant 1010, and 0.5 parts of antioxidant 168 were added; the mixture was mixed for another 10 minutes, and finally the mixture was fed into a twin-screw extruder and granulated at 160-190°C to obtain highly active G-PBS.
[0102] Step 2 and step 3 of this comparative example 1 are the same as those of the embodiment 1, and also do not include the preparation of the anti-cracking elastomer in step 4.
[0103] Step 5, the composition preparation step comprises the following steps:
[0104] Take 37 parts of M-PLA, 16 parts of G-PBS, 3 parts of the first barrier anti-degradation sustained-release agent, 3 parts of the second barrier anti-degradation sustained-release agent, 3 parts of ADX1 comprehensive additive, 5 parts of talc, and 15 parts of calcium carbonate. In this embodiment 1, no dynamic crosslinking agent is added.
[0105] The above ingredients were put into a high-speed mixer for compounding and mixing for 15 minutes, and then fed to a twin-screw extruder for granulation to obtain a composite product, code-named XP1.
[0106]
[0107] Table 1 Comparison of formulas of Example 1 and Control Example 1
[0108] Embodiment 2
[0109] Step 1, step 2 and step 3 are the same as in Example 1, and the preparation of the anti-cracking elastomer in step 4 is also not included. Take 6 parts of the modified PLA prepared in step 1, mix with 49 parts of PLA, and obtain compounded modified PLA1. 6 parts of modified PBS and 10 parts of PBS are mixed to obtain 16 parts of compounded modified PBS1.
[0110] Step 5, the composition preparation step comprises the following steps:
[0111] Take 55 parts of the above-mentioned modified PLA1, 16 parts of modified PBS1, 3 parts of the first barrier anti-degradation sustained-release agent, 3 parts of the second barrier anti-degradation sustained-release agent, 3 parts of ADX1 comprehensive additive, 5 parts of talcum powder, and 15 parts of calcium carbonate. Among them, no dynamic crosslinking agent is added in this embodiment 2. The above ingredients are put into a high-speed mixer for compounding and mixing for 15 minutes, and then fed to a twin-screw extruder for granulation to obtain a PLA durable composite product with multi-effect barrier, the product code is P2.
[0112] Comparative Example 2
[0113] Step 1 and step 2 are the same as those in control example 1.
[0114] Take 51 parts of M-PLA prepared in the above steps, 20 parts of G-PBS, 3 parts of ADX1 comprehensive additive, 11 parts of talcum powder, and 15 parts of calcium carbonate. In this comparative example 2, no dynamic crosslinking agent is added. The above ingredients are mixed in a high-speed mixer for 15 minutes, and then fed to a twin-screw extruder for granulation to obtain a composite product, the product code of which is XP2.
[0115]
[0116] Table 2 is a comparison table of the formulas of Example 2 and Example 3
[0117] The difference between Example 2 and Control Example 2 is that: Example 2 uses a composite modified mixed resin modified PLA and modified PBS, and contains a first barrier anti-degradation sustained-release agent C1 and a second barrier anti-degradation sustained-release agent C2;
[0118] The PLA and PBS resins of the comparative example 2 are M-PLA and G-PBS grafted by the conventional one-step method, and do not contain the first barrier anti-degradation sustained-release agent C1 and the second barrier anti-degradation sustained-release agent C2.
[0119] Embodiment 3
[0120] Step 1, step 2 and step 3 are the same as those in Example 1.
[0121] Step 4, the preparation of the anti-cracking elastomer comprises the following steps:
[0122] D1. Add 100 parts of EVOH resin into the vacuum dryer, set the drying temperature to 80°C, stir at a speed of 600rpm / min, and start the UV light irradiation in the dryer. While vacuum drying, the surface of the EVOH resin is activated by light for 1 hour.
[0123] D2, stop drying and irradiation, open the cover, add 2 parts of maleic anhydride MAH, 0.5 parts of ultrafine tourmaline powder with vacuum sputtering deposition nanometers on the surface, add 0.5 parts of PVA aqueous solution and 0.5 parts of silane coupling agent KH550 after mixing, continue heating and drying and UV light irradiation for 1 hour, so that MAH is connected to the surface of EVOH resin, and the solid phase grafting of EVOH resin is completed, that is, MA-EVOH is obtained;
[0124] D3. Take 30 parts of MA-EVOH resin and 70 parts of TPU resin obtained in step D2, blend them for 10 minutes, put them into twin-screw extrusion granulation, set the melt temperature to 170-185°C, and obtain a crack-resistant EVOH-TPU elastomer.
[0125] Step 5, the composition preparation step comprises the following steps:
[0126] Take 40 parts of modified PLA prepared in the above steps, 16 parts of modified PBS, 3 parts of the first barrier anti-degradation sustained-release agent (C1), 3 parts of the second barrier anti-degradation sustained-release agent (C2), 15 parts of EVOH-TPU elastomer, 3 parts of ADX1 comprehensive additive, 5 parts of talcum powder, and 15 parts of calcium carbonate. Among them, no dynamic crosslinking agent is added in this embodiment. The above ingredients are put into a high-speed mixer for compounding and mixing for 15 minutes, and then fed to a twin-screw extruder for granulation to obtain a PLA durable composite product with multiple barrier effects, the product code is P3.
[0127] Comparative Example 3
[0128] Step 1, step 2 and step 3 are the same as those in Example 3, but step 4 is not included, that is, there is no anti-cracking EVOH-TPU elastomer.
[0129] Take 55 parts of modified PLA prepared in the above steps, 16 parts of modified PBS, 3 parts of the first barrier anti-degradation sustained-release agent (C1), 3 parts of the second barrier anti-degradation sustained-release agent (C2), 3 parts of ADX1 comprehensive additive, 5 parts of talcum powder, and 15 parts of calcium carbonate. Among them, this control example does not add a dynamic crosslinking agent. Put the above ingredients into a high-speed mixer for compounding and mixing for 15 minutes, and then feed them to a twin-screw extruder for granulation to obtain a product with a product code of XP3.
[0130]
[0131] Table 3 is a comparison table of the formulas of Example 3 and Comparative Example 3
[0132] Embodiment 4
[0133] Step 1, step 2, step 3 and step 4 are the same as those in Example 3. Take 35 parts of modified PLA prepared in the above steps, 16 parts of modified PBS, 3 parts of the first barrier anti-degradation sustained-release agent (C1), 3 parts of the second barrier anti-degradation sustained-release agent (C2), 20 parts of EVOH-TPU elastomer, 3 parts of ADX1 comprehensive additive, 5 parts of talc, and 15 parts of calcium carbonate. Among them, EVOH-TPU elastomer is prepared in step 4.
[0134] The above ingredients are put into a high-speed mixer for compounding and mixing, and then fed to a twin-screw extruder for granulation to obtain a product with a product code of P4.
[0135] Embodiment 5
[0136] Step 1, step 2, step 3 and step 4 are the same as those in Example 3. Take 35 parts of modified PLA prepared in the above steps, 16 parts of modified PBS, 3 parts of the first barrier anti-degradation sustained-release agent (C1), 3 parts of the second barrier anti-degradation sustained-release agent (C2), 3 parts of ADX1 comprehensive additive, 5 parts of talcum powder, 12.9 parts of calcium carbonate, 2 parts of GMA, 0.1 parts of DCP diisopropylbenzene peroxide, and 20 parts of EVOH-TPU-GF elastomer. The composition of EVOH-TPU-GF elastomer includes 55% TPU, 30% MA-EVOH and 15% GF (glass fiber). GF (glass fiber) is added to the EVOH-TPU elastomer of Example 4 for compounding.
[0137] The above ingredients are put into a high-speed mixer for compounding and mixing, and then fed to a twin-screw extruder for granulation to obtain a product with a product code of P5.
[0138] Embodiment 6
[0139] Step 1, step 2, step 3 and step 4 are the same as those in Example 3. Take 35 parts of modified PLA prepared in the above steps, 16 parts of modified PBS, 3 parts of the first barrier anti-degradation sustained-release agent (C1), 3 parts of the second barrier anti-degradation sustained-release agent (C2), 3 parts of ADX1 comprehensive additive, 5 parts of talcum powder, 12.9 parts of calcium carbonate, 2 parts of GMA, 0.1 parts of DCP, 0.9 parts of ADX2, and 20 parts of EVOH-TPU-GF elastomer. The components of EVOH-TPU-GF elastomer include 55% TPU, 30% MA-EVOH and 15% GF (glass fiber). ADX2 is a crosslinking agent MDI (diphenylmethylmethane diisocyanate). The above components are put into a high-speed mixer for compounding and mixing, and the materials are fed to a twin-screw extruder for granulation to obtain a product with a product code of P6.
[0140]
[0141] Table 4 is a comparison table of the formulas of Examples 4, 5, and 6
[0142]
[0143] Table 5
[0144] Table 5 is a comparison of the physical properties and weight loss rate of each sample on the first day and after 45 days of high temperature and high humidity (60 degrees Cx75%RH).
[0145]
[0146] Table 6
[0147] Table 6 is a comparison of the elongation decrease of each sample on the first day and after 45 days of high temperature and high humidity (60 degrees Cx75%RH).
[0148] From the results of Table 1 and Table 4 above, the difference between Example 1 and Control Example 1 can be compared. From the data, it can be seen that the two-step composite grafting process of the present invention is significantly more effective than the traditional one-step grafting process. The initial mechanical strength (tensile strength and elongation at break) of "Example 1" is about 10-16% higher than that of Control Example 1; however, the weight loss and physical property degradation of Example 1 after aging test are significantly less than those of Control Example 1, which means that Example 1 has a longer service life, that is, it is more durable; therefore, the composition obtained by the formula and preparation method of Example 1 has more durable performance.
[0149] From the comparison between Example 1 in Table 1 and Example 2 in Table 2, it can be seen that good durability can be achieved without using only modified PLA and modified PBS in the material formula. For example, using more than 6 parts of modified PLA resin mixed with ordinary PLA resin, and using more than 6 parts of modified PBS resin mixed with ordinary PBS resin, can also achieve good performance effects. Therefore, in actual production, adjustments can be made based on the comprehensive consideration of cost and physical property requirements.
[0150] It can be seen from Table 2 and Table 4 that the two barrier anti-degradation sustained-release agents (C1 and C2) of the present invention have a good anti-decay effect on the PLA / PBS composition and can achieve the anti-degradation effect.
[0151] It can be seen from Table 4, Table 5 and Table 6 that the plant-based elastomer has obvious effects in crack resistance and water vapor barrier. In particular, after adding GF glass fiber reinforced elastomer, the impact degradation of the composition after aging can be delayed and the embrittlement can be reduced. Comparing Example 4 and Example 5 in Table 4, it can be seen that glass fiber reinforcement (EVOH-TPU-GF) has higher physical properties.
[0152] By comparing Example 5 with Example 6, it can be seen that the addition of the dynamic cross-linking agent slightly improves the physical properties of the material and also has a significant effect on reducing weight loss (delaying aging degradation).
[0153] It can also be seen from Table 6 above that the elongation of the sample of Control Example 2 decreased by 32.2% after 45 days of high temperature and high humidity, which is significantly worse than the 24.1% decrease of Example 2, indicating that the degradation of Control Example 2 is more serious due to the lack of protection of C1 and C2; reflecting that C1 and C2 can achieve the effect of anti-degradation.
[0154] The elongation of the sample in Example 3 decreased by only 17.2% after 45 days of testing, which is much better than the 21.5% decrease in the control example 3. This is because the anti-cracking elastomer EVOH-TPU component in the formula of Example 3 has played a role in water vapor barrier, so the aging degradation is much slower.
[0155] Compared with the prior art, the present invention has the following characteristics:
[0156] (1) In order to form a good binding force between the polymers, composite activation grafting is performed on each polymer. At the same time, tourmaline powder with nano-deposited on the surface is mixed before the resin is grafted. PLA resin and PBS resin are composite grafted with grafting materials (MAH and GMA) and subjected to twin-screw reaction extrusion. This unique composite grafting greatly improves the compatibility between different polymers.
[0157] (2) Multi-effect step-by-step release barrier and anti-cracking protective agent: The first barrier and anti-cracking agent is inserted into the montmorillonite by intercalation, and then wrapped by PLA and PBS resins. The second barrier and anti-cracking agent is first melted in the PVA cast film, and then the film is crushed and ground, and finally melted in the composition. The above comprehensive barrier and anti-degradation protective agent will be slowly released at different times after the composition is melted and granulated and processed for the second time, forming a ladder-like long-term and effective protection for the final product, achieving the purpose of durable use.
[0158] (3) The polymers of each component are first innovatively grafted and modified, and after mixed melting, excellent bonding forces are generated between the different polymers inside. Finally, the network crosslinking of the entire mixture is strengthened by dynamic crosslinking.
[0159] The above-described implementation methods do not constitute a limitation on the protection scope of the technical solution. Any modification, equivalent replacement and improvement made within the spirit and principle of the above-described implementation methods shall be included in the protection scope of the technical solution.
Claims
1. A PLA durable composition with multiple barrier effects, characterized in that: The invention comprises the following components in parts by weight: 6 to 55 parts of modified PLA resin, 6 to 25 parts of modified PBS resin, 5 to 20 parts of EVOH-TPU elastomer, 2 to 8 parts of the first barrier anti-degradation sustained-release agent, 2 to 10 parts of the second barrier anti-degradation sustained-release agent, 2 to 8 parts of comprehensive auxiliary agent, and 0.5 to 2 parts of dynamic cross-linking agent; The modified PLA resin comprises the following components in parts by weight: 80-100 parts of PLA resin, 4-9 parts of maleic anhydride, 0.5-2 parts of ultrafine tourmaline powder with nanomaterials deposited on the surface by vacuum sputtering, 0.5-2 parts of plasticizer, 0.5-2 parts of coupling agent, 0.02-0.05 parts of DCP diisopropylbenzene peroxide, and 1-2 parts of antioxidant; The modified PBS resin comprises the following components in parts by weight: 80-100 parts of PBS resin, 4-9 parts of GMA, 0.5-2 parts of ultrafine tourmaline powder with nanomaterials deposited on the surface by vacuum sputtering, 0.5-2 parts of plasticizer, 0.5-2 parts of coupling agent, 0.02-0.05 parts of DCP diisopropylbenzene peroxide, and 1-2 parts of antioxidant; The first barrier anti-degradation sustained-release agent comprises the following components in parts by weight: 80-100 parts of organic montmorillonite, 8-10 parts of nano zinc oxide, 15-20 parts of chitosan, 2-5 parts of PE wax, 5-10 parts of silane coupling agent, 5-20 parts of modified PLA resin, 5-20 parts of modified PBS resin, 5-10 parts of water repellent, 2-6 parts of antioxidant, and 1-2 parts of MDI diphenylmethane diisocyanate; The second barrier anti-degradation sustained-release agent comprises the following components in parts by weight: 20-70 parts of PVA polyvinyl alcohol, 20-70 parts of corn starch, 10-20 parts of polysaccharide, 0.5-2 parts of cross-linking agent, 2-30 parts of plasticizer, 0.5-2 parts of film-forming agent, 400-800 parts of deionized water, 0.5-2 parts of anti-aging agent, 0.5-2 parts of antioxidant, 0.5-2 parts of heat stabilizer, and 0.5-2 parts of antibacterial agent; The activation and composite grafting modification of PLA and PBS resins include the following steps: The first solid phase grafting of A1, PLA or PBS: a1. Add 80-100 parts of PLA or PBS resin into a vacuum dryer, set the drying temperature to 60-80°C, stir at a speed of 400-800 r / min, and start the UV light irradiation in the dryer. While vacuum drying, perform light activation on the surface of the PLA or PBS resin for 1-1.5 hours. a2. Stop drying and irradiation and open the cover, add 2-5 parts of maleic anhydride or 2-5 parts of GMA, 0.5-2 parts of ultrafine tourmaline powder with nanomaterials deposited on the surface by vacuum sputtering, mix the above materials, add 0.5-2 parts of plasticizer, 0.5-2 parts of coupling agent, continue heating and drying and UV light irradiation for 20-60 minutes, and the first stage of solid phase grafting of PLA or PBS is completed: A2, the second solid phase grafting of PLA or PBS: The first solid-phase grafted PLA or PBS resin prepared in step a2 is transferred into a high-speed mixer, and then 2 to 4 parts of maleic anhydride or 2 to 4 parts of GMA, 0.02 to 0.05 parts of DCP, and 1 to 2 parts of antioxidant are added, and mixed for 10 to 15 minutes. Finally, the mixture is put into a twin-screw extruder for granulation to obtain a low-initiator high-activity composite grafted modified PLA or PBS resin; The first step of preparing the barrier anti-degradation sustained-release agent comprises the following steps: B1. Add 80-100 parts of organic montmorillonite, 8-10 parts of nano zinc oxide, 15-20 parts of chitosan, and 2-5 parts of PE wax into a high-speed mixer and mix them at a speed of 800-1000 r / min for 20-30 minutes; B2, pour in 5-10 parts of silane coupling agent, 5-20 parts of modified PLA, 5-20 parts of modified PBS, 5-10 parts of water repellent, 2-6 parts of antioxidant, and 1-2 parts of MDI diphenylmethane diisocyanate, continue to mix at high speed for 10-20 minutes, and then feed the material into a twin-screw granulator to make particles, that is, the first barrier anti-degradation sustained-release agent is obtained; The second barrier anti-degradation sustained-release agent preparation step comprises the following steps: C1. Take 20-70 parts of PVA polyvinyl alcohol, 20-70 parts of corn starch, 10-20 parts of polysaccharide, 0.5-2 parts of cross-linking agent, 2-30 parts of plasticizer, 0.5-2 parts of film-forming agent, 400-800 parts of deionized water, 0.5-2 parts of anti-aging agent, 0.5-2 parts of antioxidant, 0.5-2 parts of heat stabilizer, 0.5-2 parts of antibacterial agent, put the above components into a high-speed mixer, mix them, and then add deionized water to dilute them into a mixed solution with a mass concentration of 30-40%; C2. Heat the mixed solution to 70-90°C and stir at a speed of 50-150 r / min for 50-60 minutes, then pour it onto a glass plate to form a film, let it cool for 2-3 hours, crush the film and sieve it into 200-500 mesh particles to obtain a second barrier anti-degradation sustained-release agent.
2. The PLA durable composition with multiple-effect barrier properties according to claim 1, characterized in that: The vacuum sputtering deposited nano material on the surface of the ultrafine tourmaline powder is TiOx and / or SiOx, wherein x=0.5, or x=1, or x=1.5, or x=2.
3. A method for preparing a PLA durable composition with multiple barrier effects, characterized in that: The method for preparing the PLA durable composition with multi-effect barrier as claimed in any one of claims 1 to 2 comprises the following steps: The activation and composite modification step is used to activate and composite graft modification of PLA and PBS resins; A first barrier and anti-degradation sustained-release agent preparation step, for preparing a first barrier and anti-degradation sustained-release agent; A second barrier and anti-degradation sustained-release agent preparation step, used to prepare a second barrier and anti-degradation sustained-release agent; A crack-resistant elastomer preparation step for preparing a crack-resistant EVOH-TPU elastomer; The composition preparation step is used to extrude and granulate the above ingredients to obtain a PLA durable composition with multiple barrier effects.
4. The method for preparing the PLA durable composition with multiple-effect barrier properties according to claim 3, characterized in that: The step of preparing the anti-cracking elastomer comprises the following steps: D1. Add 80-100 parts of EVOH resin into the vacuum dryer, set the drying temperature to 70-80℃, stir at a speed of 400-600r / min, and start the UV light irradiation in the dryer. While vacuum drying, the surface of the EVOH resin is activated by light for 1-2 hours. D2, stop drying and irradiation, open the cover, add 2-5 parts of maleic anhydride MAH, 0.5-2 parts of ultrafine tourmaline powder with nanomaterials deposited on the surface by vacuum sputtering, add 0.5-2 parts of PVA aqueous solution and 0.5-2 parts of silane coupling agent after mixing, continue heating and drying and UV light irradiation for 1-2 hours, and complete the solid phase grafting of EVOH resin; D3. Take 30-40 parts of the solid-phase grafted EVOH resin obtained in step D2 and 70-80 parts of TPU resin, blend them for 10-20 minutes, and put them into twin-screw extrusion granulation to obtain a crack-resistant EVOH-TPU elastomer.
5. The method for preparing the PLA durable composition with multiple-effect barrier properties according to claim 3, characterized in that: The composition preparation step comprises the following steps: Take 6-55 parts of modified PLA, 10-20 parts of modified PBS, 5-20 parts of EVOH-TPU elastomer, 2-8 parts of the first barrier anti-degradation sustained-release agent, 2-10 parts of the second barrier anti-degradation sustained-release agent, 2-8 parts of comprehensive additives, and 0.5-2 parts of dynamic cross-linking agent; The above ingredients are put into a high-speed mixer for compounding and mixing for 10 to 20 minutes, and then fed into a twin-screw melt dynamic cross-linking extrusion granulation to obtain a PLA durable composition with multiple barrier effects.
Citation Information
Patent Citations
Fully-degradable high-barrier composite material for flexible package as well as preparation method and application thereof
CN110791069A
Biodegradable straw and preparation method thereof
CN112538239A